Institutional geodiagnosis of the Dr. Carlos Gomes de Barros of the city of União dos Palmares - AL / Geodiagnose institucional da Escola Estadual Dr. Carlos Gomes de Barros da cidade de União dos Palmares - AL - Marcio Emidio da Silva; Josecleide Maria da Silva; Edna Augostinho Sena; Sirlange Soares da Silva Brito; Everaldo Timóteo da Silva; Salus Manoel Pessoa da Silva (Universidade Estadual de Alagoas, 2016)
This article aims to expose the results and analysis of the institutional aspects made in the State School Carlos Gomes de Barros about the physical, educational and administrative spaces. These data are intended to verify the process of teaching and learning in school and to support the study of the Education City in Geography, as the proposed sub-project of which we are part. The methodology used for data collection occurred from the use of questionnaires and subsequent data processing. And authors who work with the issue said. Multiple theoretical and methodological looks in teacher training, which aims to set new methodologies that will facilitate the process of teaching and learning in public school systems of Alagoas, as well as the appreciation of the teaching profession among students of degrees from the State University of Alagoas and teachers in service. With the Theoretical Foundation, authors such as Vygotsky and Morales. Thus, through these data collections can identify the profile of the school development generally.